Critically Analysing the Relevancy of Medical and Forensic Evidences in Sexual Offence - Shukla, Prakhar (Trinity Law Review, 2023)
India is a developing country where women participate in the growth of the country in the same way that men do. From the beginning to the present, women have made themselves present in every aspect of progress, whether it is sports, politics, or science. There are still several factors that contribute to women’s mistreatment. And one of the said elements is sexual offence.